Steel material for sliding parts and manufacturing method thereof
A steel material with a controlled chemical composition and microstructure addresses the balance of mechanical strength, wear resistance, and workability, enhancing sliding properties and workability for sliding parts in harsh environments.
Patent Information
- Application Number
- JP2020184795
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-28
- Filing Date
- 2020-11-05
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2040-11-05
AI Technical Summary
Existing steel materials for sliding parts face challenges in achieving a balance between mechanical strength, wear resistance, and workability, particularly in harsh environments, and existing techniques are not applicable to hypoeutectoid steel.
A steel material with a specific chemical composition and controlled microstructure, including a surface layer with 30-80% pearlite, 30-60% martensite/bainite, and ferrite, and a lamella spacing of 90-200 nm, combined with controlled cooling rates to achieve Vickers hardness of Hv270-300, is developed.
The steel material exhibits excellent sliding properties and workability, reducing friction and wear, making it suitable for applications like crankshafts in severe conditions.
Smart Images

Figure 0007617372000004 
Figure 0007617372000001 
Figure 0007617372000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a steel material for sliding parts and a method for manufacturing a steel material for sliding parts. [Background technology]
[0002] Steel materials are widely used in industrial products such as automobile parts, railway vehicle parts, building materials, pipes, etc. Since steel materials have higher mechanical strength than other metal materials, they are used as materials for so-called sliding parts, such as power transmission parts, such as gears and shafts.
[0003] The biggest issue with sliding parts is friction and wear between parts, which are thought to be the cause of malfunctions and reduced efficiency in the entire mechanical system. As mechanical systems become smaller and lighter in the future, the environment in which sliding parts live is expected to become even more severe. For example, as automobile engine parts such as crankshafts become smaller and lighter, they will be required to be resistant to seizure in more severe environments. To solve these problems, it is necessary to develop steel materials for sliding parts with superior mechanical strength to current products, and to prepare for the reduction in size and weight of entire mechanical systems.
[0004] Increasing the hardness of steel materials is one way to improve the mechanical strength of sliding parts. However, increasing the hardness of steel materials impairs the workability of the steel materials, which is risky when mass-producing parts. Therefore, a method of selectively controlling the structure of only the surface layer and hardening only that part is effective in improving the sliding properties of sliding parts.
[0005] For example, Japanese Patent Laid-Open Publication No. 1-230746 discloses that in a sliding component having a fixed member made of cast iron and a sliding member made of a material harder than cast iron, the surface layer structure of the fixed member is made to be a hardened layer made of martensite or a mixed phase structure of martensite, pearlite, ferrite, and graphite, and a structure made of oxides.
[0006] In addition, it is also effective to suppress wear by refining the structure and increasing the crystal strength by adding metal elements such as Cr and Mo. For example, JP 2018-44226 A discloses a method for producing a wear-resistant iron-based sintered alloy using an iron alloy powder containing 2.5 to 3.5 mass% Cr and 0.4 to 0.6 mass% Mo. In addition, JP 2017-48441 A discloses that in a seamless steel pipe made of fine pearlite and ferrite and having a hardness of Hv250 to 300, the strength is improved by adding one or more of Ti, Cr, Ni, Cu, Mo, and Nb.
[0007] Japanese Patent No. 5660220 discloses a medium carbon steel sheet having an average carbide diameter of 0.4 μm or less, a spheroidization rate of 90% or more, and an average ferrite grain size of 10 μm or more. The same publication also describes that the average lamellar thickness of cementite in pearlite contained in the coiled steel is 0.02 to 0.5 μm. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Japanese Patent Application Publication No. 1-230746 [Patent Document 2] JP 2018-44226 A [Patent Document 3] JP 2017-48441 A [Patent Document 4] Patent No. 5660220 Summary of the Invention [Problem to be solved by the invention]
[0009] JP 1-230746 A controls the surface structure of a fixed member made of cast iron, and the same technology cannot be applied to hypo-eutectoid steel. JP 2018-44226 A, JP 2017-48441 A, and JP 5660220 A do not relate to steel materials for sliding parts, and the sliding properties are unclear.
[0010] An object of the present invention is to provide a steel material for sliding parts having excellent sliding properties and workability. Another object of the present invention is to provide a method for manufacturing a steel material for sliding parts having excellent sliding properties and workability. [Means for solving the problem]
[0011] A steel material for sliding parts according to one embodiment of the present invention has a chemical composition, in mass%, of C: 0.15-0.65%, Si: 0.05-0.60%, Mn: 0.40-1.70%, P: 0.03% or less, S: 0.070% or less, Al: 0.005-0.060%, N: 0.001-0.020%, Cr: 0-0.35%, and the balance: Fe and impurities. The ...
[0012] A manufacturing method of a steel material for sliding parts according to one embodiment of the present invention is a method for manufacturing the above-mentioned steel material for sliding parts, the chemical composition of which is, in mass%, C: 0.42-0.48%, Si: 0.05-0.60%, Mn: 0.60-0.90%, P: 0.03% or less, S: 0.035% or less, Al: 0.005-0.060%, N: 0.001-0.020%, Cr: 0-0.35%, balance: Fe and impurities, and the method includes the steps of heating a material to a heating temperature of 720-770°C, and cooling the material so that the average cooling rate in the temperature range from the heating temperature to 250°C is 40.0-50.0°C / sec.
[0013] A manufacturing method of a steel material for sliding parts according to one embodiment of the present invention is a method for manufacturing the above-mentioned steel material for sliding parts, the chemical composition of which is, in mass%, C: 0.35-0.41%, Si: 0.05-0.60%, Mn: 1.35-1.65%, P: 0.03% or less, S: 0.070% or less, Al: 0.005-0.060%, N: 0.001-0.020%, Cr: 0-0.35%, balance: Fe and impurities, the method comprising the steps of heating a material to a heating temperature of 720-950°C, and cooling the material so that the average cooling rate in the temperature range from the heating temperature to 250°C is 2.0-7.0°C / sec. Effect of the Invention
[0014] According to the present invention, a steel material for sliding parts having excellent sliding properties and workability can be obtained. [Brief description of the drawings]
[0015] [Figure 1] Figure 1 is a graph showing the results of a ball-on-disk type friction and wear test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present inventors investigated the sliding properties and workability of various steel materials in order to develop a steel material having excellent sliding properties and workability. In particular, they focused on the structure of the steel material and investigated the sliding properties and workability for each structure. As a result, they obtained the following findings.
[0017] The best friction coefficient is exhibited by a steel material having a Vickers hardness of Hv 270 to 300. The structure of the steel material preferably contains pearlite, at least one of martensite and bainite, and ferrite, with the volume fraction of pearlite being 30 to 80%.
[0018] By including the hard structure of martensite or bainite, it is possible to make the steel harder than steel made of ferrite and pearlite. On the other hand, if the hardness is made too high, not only does the workability decrease, but the friction coefficient also increases. This is thought to be because the wear resistance decreases due to the decrease in toughness and ductility.
[0019] The precipitated carbides are an important factor that affects the hardness and workability of the steel material as well as the sliding properties of the steel material. In order to improve the sliding properties and workability of the steel material, it is necessary to control the lamellar spacing of pearlite. Specifically, the lamellar spacing of pearlite is preferably set to 90 to 200 nm in terms of the balance between hardness and sliding properties.
[0020] Based on the above findings, the present invention has been completed. A steel material for sliding parts according to one embodiment of the present invention will be described in detail below.
[0021] [Chemical composition] The steel material for sliding parts according to this embodiment has the chemical composition described below. In the following description, "%" for the content of an element means mass %.
[0022] C: 0.15-0.65% Carbon (C) improves the hardenability of steel and contributes to improving hardness. On the other hand, if the C content is too high, the machinability of the steel decreases, and the workability decreases. Therefore, the C content is 0.15 to 0.65%. The lower limit of the C content is preferably 0.20%, and more preferably 0.22%. The upper limit of the C content is preferably 0.50%, and more preferably 0.48%.
[0023] Silicon: 0.05 to 0.60% Silicon (Si) has a deoxidizing effect and an effect of strengthening ferrite. On the other hand, if the Si content is too high, the machinability of the steel decreases, and the workability decreases. Therefore, the Si content is 0.05 to 0.60%. The lower limit of the Si content is preferably 0.10%, and more preferably 0.15%. The upper limit of the Si content is preferably 0.50%, and more preferably 0.35%.
[0024] Mn: 0.40-1.70% Manganese (Mn) improves the hardenability of steel and contributes to improving hardness. On the other hand, if the Mn content is too high, the hot workability of the steel decreases. Therefore, the Mn content is 0.40 to 1.70%. The lower limit of the Mn content is preferably 0.50%, and more preferably 0.60%. The upper limit of the Mn content is preferably 1.60%, and more preferably 1.50%.
[0025] Al: 0.005 to 0.060% Aluminum (Al) forms nitrides and contributes to the refinement of crystal grains. On the other hand, if the Al content is too high, the machinability of the steel decreases, and the workability decreases. Therefore, the Al content is 0.005 to 0.060%. The lower limit of the Al content is preferably 0.010%, and more preferably 0.020%. The upper limit of the Al content is preferably 0.050%, and more preferably 0.045%.
[0026] N: 0.001 to 0.020% Nitrogen (N) forms nitrides and carbonitrides, and contributes to the refinement of crystal grains. On the other hand, if the N content is too high, the hot ductility of the steel decreases. Therefore, the N content is 0.001 to 0.020%. The lower limit of the N content is preferably 0.002%. The upper limit of the N content is preferably 0.015%, and more preferably 0.010%.
[0027] P:0.03% or less Phosphorus (P) is an impurity. If the P content is too high, the fatigue strength of the steel decreases. Therefore, the P content is 0.03% or less. The P content is preferably 0.025% or less, and more preferably 0.02% or less.
[0028] S: 0.070% or less Sulfur (S) is an impurity. If the S content is too high, the hot workability of the steel is reduced. Therefore, the S content is 0.070% or less. The S content is preferably 0.065% or less, and more preferably 0.060% or less. S may be intentionally added to improve the machinability of the steel. In this case, the lower limit of the S content is preferably 0.020%, and more preferably 0.030%.
[0029] The balance of the chemical composition of the steel material for sliding parts according to the present embodiment is Fe and impurities. The impurities referred to here are elements that are mixed in from ores or scraps used as raw materials for the steel, or elements that are mixed in from the environment during the manufacturing process, etc.
[0030] The chemical composition of the steel material for sliding parts according to the present embodiment may contain Cr instead of a part of the Fe described above. Cr is an optional element. That is, the chemical composition of the steel material for sliding parts according to the present embodiment may not contain Cr.
[0031] Cr: 0~0.35% Chromium (Cr) improves the hardenability of steel and contributes to improving hardness. This effect can be obtained even if even a small amount of Cr is contained. On the other hand, if the Cr content exceeds 0.35%, the two-phase region becomes narrow, making it difficult to obtain a desired structure. In addition, carbides tend to precipitate. Therefore, the Cr content is 0 to 0.35%. The lower limit of the Cr content is preferably 0.01%, and more preferably 0.03%. The upper limit of the Cr content is preferably 0.20%, and more preferably 0.10%.
[0032] As one aspect, the steel material for sliding parts according to this embodiment may have a chemical composition, in mass%, of C: 0.30 to 0.55%, Si: 0.05 to 0.60%, Mn: 0.40 to 1.20%, P: 0.03% or less, S: 0.035% or less, Al: 0.005 to 0.060%, N: 0.001 to 0.020%, Cr: 0 to 0.35%, and the balance: Fe and impurities.
[0033] In this embodiment, the lower limit of the C content is preferably 0.35%, more preferably 0.42%. The upper limit of the C content is preferably 0.50%, more preferably 0.48%. The upper limit of the Mn content is preferably 1.00%, more preferably 0.90%. The upper limit of the S content is preferably 0.030%, more preferably 0.025%.
[0034] As another aspect, the steel material for sliding parts according to this embodiment may have a chemical composition, in mass%, of C: 0.42 to 0.48%, Si: 0.05 to 0.60%, Mn: 0.60 to 0.90%, P: 0.03% or less, S: 0.035% or less, Al: 0.005 to 0.060%, N: 0.001 to 0.020%, Cr: 0 to 0.35%, and the balance: Fe and impurities.
[0035] As another aspect, the steel material for sliding parts according to this embodiment may have a chemical composition, in mass%, of C: 0.35 to 0.41%, Si: 0.05 to 0.60%, Mn: 1.35 to 1.65%, P: 0.03% or less, S: 0.070% or less, Al: 0.005 to 0.060%, N: 0.001 to 0.020%, Cr: 0 to 0.35%, and the balance: Fe and impurities.
[0036] [Organization] The steel material for sliding parts according to this embodiment includes a portion in which the structure from at least the surface to a depth of 10 μm is a structure containing 30 to 80% by volume of pearlite, at least one of martensite and bainite, and ferrite.
[0037] Pearlite hardens during sliding and contributes to improving wear resistance. If the volume fraction of pearlite is too low, this effect is not sufficiently obtained. On the other hand, if the volume fraction of pearlite is too high, the volume fractions of martensite, bainite, and ferrite cannot be ensured, making it difficult to maintain a balance between hardness and workability. Therefore, the volume fraction of pearlite is 30 to 80%. The lower limit of the volume fraction of pearlite is preferably 31%, and more preferably 32%. The upper limit of the volume fraction of pearlite is preferably 78%, and more preferably 76%.
[0038] Both martensite and bainite are hard structures and contribute to improving the hardness of steel. If the structure does not contain any of martensite and bainite, it is difficult to achieve a Vickers hardness of Hv270 or more. The lower limit of the sum of the volume fraction of martensite and the volume fraction of bainite is preferably 3%, more preferably 5%, and more preferably 10%. On the other hand, if the sum of the volume fraction of martensite and the volume fraction of bainite is too high, good sliding properties cannot be obtained and the workability is also reduced. The upper limit of the sum of the volume fraction of martensite and the volume fraction of bainite is preferably 60%, more preferably 58%, and more preferably 56%.
[0039] In a structure in which martensite and bainite are mixed, it is often difficult to accurately distinguish between them. Therefore, in this embodiment, martensite and bainite are not strictly distinguished from each other, and the sum of the volume fraction of martensite and the volume fraction of bainite is used as an index of the structure. On the other hand, since martensite is a harder structure than bainite, a structure in which the ratio of martensite to bainite is obviously high has a higher Vickers hardness. In order to achieve a Vickers hardness within a predetermined range even in a structure in which the ratio of martensite to bainite is particularly high, it is preferable to set the upper limit of the sum of the volume fraction of martensite and the volume fraction of bainite to 30%. In this case, the upper limits of the volume fraction of martensite and the volume fraction of bainite are more preferably 26%, and more preferably 24%. In this case, the lower limit of the volume fraction of pearlite is preferably 61%. In this case, the lower limit of the volume fraction of pearlite is more preferably 62%, and more preferably 65%.
[0040] Ferrite is a soft structure and contributes to improving the workability of steel. The lower limit of the volume fraction of ferrite is preferably 3%, more preferably 5%, and even more preferably 10%. On the other hand, if the volume fraction of ferrite is too high, it becomes difficult to achieve a Vickers hardness of Hv270 or more. The upper limit of the volume fraction of ferrite is preferably 32%, more preferably 26%, and even more preferably 20%.
[0041] The influence of sliding extends to a depth of about 5 μm from the surface. Therefore, sufficient effects can be obtained if the structure at least from the surface to a depth of 10 μm (hereinafter referred to as the "surface structure") is the above-mentioned structure. In other words, the structure located deeper than 10 μm from the surface does not significantly affect the sliding properties. Therefore, the structure located deeper than 10 μm from the surface may be a structure other than the above-mentioned structure.
[0042] However, the thickness of the structure to be controlled is arbitrary and may be adjusted depending on the purpose. The thickness of the above-mentioned structure is preferably 20 μm or more, more preferably 50 μm or more. There is no particular upper limit, and the above-mentioned structure may be present up to the core.
[0043] In the steel material for sliding parts according to this embodiment, only the surface layer structure of a specific portion of the steel material (hereinafter referred to as the "specific portion") may have the above-mentioned structure. For example, if the sliding part is a crankshaft, only the surface layer structure of the journal or pin portion may have the above-mentioned structure. In the steel material for sliding parts according to this embodiment, the entire steel material may have the above-mentioned structure.
[0044] The surface layer structure of the steel material for sliding parts according to the present embodiment may contain structures other than pearlite, martensite, bainite, and ferrite. The volume fraction of structures other than pearlite, martensite, bainite, and ferrite contained in the surface layer structure of the steel material for sliding parts according to the present embodiment is preferably 5% or less, more preferably 3% or less, and even more preferably 1% or less.
[0045] The volume fraction of the surface structure of a specific portion is measured as follows: A sample including the surface is taken from a specific portion of the steel material for sliding parts. A surface perpendicular to the surface is used as the observation surface, and etching is performed using mechanical polishing and electrolytic polishing. SEM images and EBSD images are observed to determine the area fraction of each structure. Measurements are made at five or more locations, and the average value is calculated, and this value is regarded as the volume fraction of each structure.
[0046] [Lamellar Spacing] In the steel material for sliding parts according to this embodiment, in the specific portion described above, the lamellar spacing of pearlite at least from the surface to a depth of 10 μm is 90 to 200 nm.
[0047] If the lamellar spacing of pearlite is too large or too small, good sliding properties cannot be obtained. In addition, if the lamellar spacing of pearlite is too large, it is difficult to make the Vickers hardness Hv270 or more. On the other hand, if the lamellar spacing of pearlite is too small, it is difficult to make the Vickers hardness Hv300 or less. Therefore, the lamellar spacing of pearlite is 90 to 200 nm. The lower limit of the lamellar spacing of pearlite is preferably 95 nm, more preferably 100 nm. The upper limit of the lamellar spacing of pearlite is preferably 180 nm, more preferably 160 nm.
[0048] The reason for specifying the lamellar spacing of pearlite from the surface to a depth of 10 μm is the same as that for the volume fraction of the structure. The lamellar spacing at a position deeper than 10 μm from the surface may be outside the above-mentioned range. Even if the thickness of the structure containing pearlite, at least one of martensite and bainite, and ferrite is 10 μm or more, the lamellar spacing does not need to be in the above-mentioned range throughout the thickness, and it is sufficient that the lamellar spacing of pearlite from the surface to a depth of 10 μm is in the above-mentioned range.
[0049] However, the thickness for controlling the lamellar spacing of pearlite is arbitrary and may be adjusted depending on the purpose. The thickness for which the lamellar spacing of pearlite is in the above-mentioned range is preferably 20 μm or more, and more preferably 50 μm or more.
[0050] The lamellar spacing of pearlite is measured as follows: A sample including the surface is taken from a specific portion of the steel material for sliding parts. A surface perpendicular to the surface is used as the observation surface, and etching is performed by mechanical polishing and electrolytic polishing. An SEM image at a magnification of 5000 times or more is observed, and the distance from the center of the thickness direction of the precipitated cementite to the center of the thickness direction of the adjacent precipitated cementite is measured, and the average value of measurements at three or more points is taken as the lamellar spacing.
[0051] [Vickers hardness] The steel material for sliding parts according to this embodiment has a Vickers hardness of Hv270 to 300 at least from the surface to a depth of 10 μm in the specific portion described above.
[0052] If the Vickers hardness is too high or too low, good sliding properties cannot be obtained. Moreover, if the Vickers hardness is too high, the workability decreases. Therefore, the Vickers hardness is Hv270 to 300. The lower limit of the Vickers hardness is preferably Hv275, and more preferably Hv280. The upper limit of the Vickers hardness is preferably Hv295, and more preferably Hv290.
[0053] The reason for specifying the Vickers hardness from the surface to a depth of 10 μm is the same as that for the volume fraction of the structure. The Vickers hardness at a position deeper than 10 μm from the surface may be outside the above-mentioned range. However, the thickness for controlling the Vickers hardness is arbitrary and may be adjusted depending on the purpose. The thickness for which the Vickers hardness falls within the above-mentioned range is preferably 20 μm or more, more preferably 50 μm or more.
[0054] Vickers hardness can be measured in accordance with JIS Z 2244 (2009) by taking a sample including the surface from a specific part of steel for sliding parts, and using a surface perpendicular to the surface as the test surface. The test force is 1 kgf (9.807 N), and the average value of measurements taken at five or more points is the Vickers hardness. The Vickers hardness of the part close to the surface can be measured at each indentation depth by performing nanoindentation on the surface.
[0055] [Coefficient of friction] The steel material for sliding parts according to this embodiment preferably has a friction coefficient of 0.25 or less in the above-mentioned specific portion.
[0056] [Manufacturing method] Hereinafter, a method for producing a steel material for sliding parts according to this embodiment will be described.
[0057] A material having the above-mentioned chemical composition is prepared. The material is, for example, a hot forged product. For example, a steel having the above-mentioned chemical composition is melted, and then subjected to continuous casting or blooming to produce a steel billet, which is then hot forged to be processed into a rough shape of a sliding part, which can be used as the material. The material after hot forging may be subjected to cutting or other processing.
[0058] At least a portion of the material is heated to a predetermined heating temperature and maintained for a predetermined period of time.
[0059] If the holding time is too short, the desired structure cannot be obtained stably. On the other hand, if the holding time is too long, the crystal grains become coarse. The lower limit of the holding time is preferably 900 seconds, more preferably 1200 seconds, and more preferably 1500 seconds. The upper limit of the holding time is preferably 3600 seconds, more preferably 3000 seconds, and more preferably 2700 seconds.
[0060] The heated portion is then cooled at a predetermined rate. If the average cooling rate in the temperature range from the heating temperature to 250°C is too small or too large, the desired structure, lamellar spacing of pearlite, and Vickers hardness cannot be obtained. Specifically, if the cooling rate in this temperature range is too small, the volume fraction of ferrite increases and the volume fraction of pearlite decreases, the lamellar spacing of pearlite may become excessively large, or the Vickers hardness may become excessively low. On the other hand, if the cooling rate in this temperature range is too large, the volume fraction of pearlite may become small, the lamellar spacing of pearlite may become excessively small, or the Vickers hardness may become excessively high.
[0061] The cooling rate in the temperature range below 250°C is arbitrary. However, if the temperature range below 250°C is cooled strongly, cracks may occur due to transformation expansion. Therefore, the cooling rate in the temperature range below 250°C is preferably 50.0°C / sec or less.
[0062] The above heating and cooling may be performed, for example, by high-frequency induction heating only on the surface layer of the material, or may be performed on the entire material in a heat treatment furnace.
[0063] After cooling, it is preferable not to perform tempering in order to prevent carbides from precipitating in the martensite. The steel material for sliding parts according to this embodiment is unlikely to suffer from delayed fracture even if tempering is not performed.
[0064] Next, the heating temperature and the cooling rate will be described in detail. In the above-mentioned manufacturing method, either (1) cooling the material from the two-phase region or (2) slow cooling in a predetermined temperature range is carried out according to the chemical composition of the material. More specifically, according to the chemical composition of the material, (1) heating the material to a heating temperature of 720 to 770°C, and then cooling the material so that the average cooling rate in the temperature range from the heating temperature to 250°C is 40.0 to 50.0°C / sec, or (2) heating the material to a heating temperature of 720 to 950°C, and then cooling the material so that the average cooling rate in the temperature range from the heating temperature to 250°C is 2.0 to 7.0°C / sec.
[0065] In the case of a material with relatively low hardenability (for example, a material having a chemical composition, by mass%, of C: 0.42 to 0.48%, Si: 0.05 to 0.60%, Mn: 0.60 to 0.90%, P: 0.03% or less, S: 0.035% or less, Al: 0.005 to 0.060%, N: 0.001 to 0.020%, Cr: 0 to 0.35%, and the balance: Fe and impurities), the material is manufactured as described above in (1).
[0066] The lower limit of the heating temperature when produced by the above method (1) is preferably 730° C. The upper limit of the heating temperature when produced by the above method (1) is preferably 760° C. The lower limit of the average cooling rate when produced by the above method (1) is preferably 42.0° C. / sec. The upper limit of the average cooling rate when produced by the above method (1) is preferably 48.0° C. / sec, more preferably 46.0° C. / sec.
[0067] When produced by the above method (1), the ratio of martensite to bainite tends to be high.
[0068] Therefore, in the case of a material with relatively low hardenability (for example, a material having a chemical composition, in mass%, of C: 0.42-0.48%, Si: 0.05-0.60%, Mn: 0.60-0.90%, P: 0.03% or less, S: 0.035% or less, Al: 0.005-0.060%, N: 0.001-0.020%, Cr: 0-0.35%, and the balance: Fe and impurities), it is preferable that the volume fraction of pearlite is 61-80%, the sum of the volume fraction of martensite and the volume fraction of bainite is 3-30%, and the volume fraction of ferrite is 3-32%.
[0069] On the other hand, in the case of a material with relatively high hardenability (for example, a material having a chemical composition, by mass%, of C: 0.35 to 0.41%, Si: 0.05 to 0.60%, Mn: 1.35 to 1.65%, P: 0.03% or less, S: 0.070% or less, Al: 0.005 to 0.060%, N: 0.001 to 0.020%, Cr: 0 to 0.35%, and the balance: Fe and impurities), it is manufactured according to the above method (2).
[0070] The lower limit of the heating temperature when produced by the above method (2) is preferably 730° C. The upper limit of the heating temperature when produced by the above method (2) is preferably 940° C. The lower limit of the average cooling rate when produced by the above method (2) is preferably 3.0° C. / sec, more preferably 4.0° C. / sec. The upper limit of the average cooling rate when produced by the above method (2) is preferably 6.0° C. / sec.
[0071] In addition, when produced by the above (2), the lamellar spacing of pearlite tends to become large.
[0072] Therefore, in the case of a material with relatively high hardenability (for example, a material having a chemical composition, in mass%, of C: 0.35 to 0.41%, Si: 0.05 to 0.60%, Mn: 1.35 to 1.65%, P: 0.03% or less, S: 0.070% or less, Al: 0.005 to 0.060%, N: 0.001 to 0.020%, Cr: 0 to 0.35%, and the remainder: Fe and impurities), the lamellar spacing of pearlite is preferably 150 to 200 nm.
[0073] The above describes the steel material for sliding parts according to one embodiment of the present invention. The steel material for sliding parts according to this embodiment has excellent sliding properties and workability. Therefore, the steel material for sliding parts according to this embodiment is suitable as a material for sliding parts. The sliding part is, for example, a crankshaft. EXAMPLES
[0074] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0075] A 150 kg piece of steel having the chemical composition shown in Table 1 was melted in a vacuum induction melting furnace (VIM) to produce an ingot.
[0076] [Table 1]
[0077] This ingot was hot forged at 950 to 1200°C to a thickness of 130 mm, width of 130 mm, and length of 1120 mm, then rolled to a thickness of 7 mm, width of 160 mm, and cut to a length of 500 mm, and then subjected to the heat treatment described in Table 2. The structure before the heat treatment was a ferrite-pearlite structure.
[0078] [Table 2]
[0079] A test piece measuring 20 mm square and 2 mm thick was taken from the center of the thickness direction of the heat-treated steel plate. The surface of the test piece (20 mm × 20 mm surface) was mirror-finished. Since a bulk structure was obtained in this example, the surface of the test piece was used as the observation surface or test surface to measure the structure, pearlite lamellar spacing, and Vickers hardness. Except for using the surface of the test piece as the observation surface or test surface, measurements were performed according to the method described in the embodiment. The results are shown in Table 2 above.
[0080] In Table 2, "P", "M+B", and "F" respectively indicate the volume fraction of pearlite, the sum of the volume fraction of martensite and the volume fraction of bainite, and the volume fraction of ferrite. However, the structures of test pieces Nos. 28 and 29 were mainly composed of tempered martensite, not martensite.
[0081] The conditions of the heat treatment applied to the steel plate are listed in the "Heat treatment conditions" column of Table 2. For example, "770°C x 1800 seconds → water cooling (47°C / second)" for test piece No. 1 indicates that the steel plate was held at 770°C for 1800 seconds, and then water-cooled at an average cooling rate of 47°C / second up to 250°C.
[0082] After the heat treatment, test pieces measuring 20 mm x 20 mm and 2 mm thick were taken from the steel sheets, and ball-on-disk type friction and wear tests were carried out using these test pieces to evaluate the sliding properties. The test machine used was a Tribometer manufactured by CSM Instruments.
[0083] The surface of the test piece was roughly polished using #1000 abrasive grains, and finally mirror-finished using 0.3 μm diamond slurry. An alumina ball with a diameter of 6 mm was used, and the friction test was carried out under the following conditions: load: 10 N, test temperature: room temperature, rotation diameter: 6 mm, friction speed: 10 mm / sec, no lubricant. The friction coefficient was the value provided by the testing machine's software. A friction coefficient of 0.25 or less at a sliding distance of 800 mm was evaluated as "good", and any other was evaluated as "unacceptable".
[0084] For workability, those with a Vickers hardness of Hv300 or less were rated "good," and those with a Vickers hardness of over Hv300 were rated "bad." For the overall evaluation, those with both "good" sliding properties and workability were rated "passed," and those with either "bad" sliding properties or workability were rated "failed." The results are shown in Table 3.
[0085] [Table 3]
[0086] As shown in Tables 2 and 3, the steels of test piece numbers 1 to 11 had pearlite volume fractions of 30 to 80%, pearlite lamellar spacings of 90 to 200 nm, and Vickers hardnesses of Hv 270 to 300. These steels had friction coefficients of 0.25 or less and exhibited excellent sliding properties.
[0087] The steel material of test piece No. 12 had poor sliding properties, which was believed to be due to the volume fraction of pearlite being too high.
[0088] The steels of test pieces Nos. 13 and 14 were inferior in sliding properties and workability, which is believed to be because the lamellar spacing of pearlite was too small.
[0089] The steel material of test piece No. 15 was inferior in sliding properties and workability, which is believed to be because the volume fraction of pearlite was too low.
[0090] The steel materials of test piece numbers 16 to 22 and 31 had poor sliding properties, which was believed to be because the volume fractions of martensite and bainite were too small.
[0091] The steel materials of test piece numbers 23 to 27 and 30 had their structures adjusted to martensite. These steel materials were inferior in sliding properties and workability.
[0092] The steel materials of test piece numbers 28 and 29 had structures adjusted to tempered martensite. These steel materials had poor sliding properties.
[0093] Figure 1 is a graph showing the results of ball-on-disk type friction and wear tests on test pieces No. 3, 16 (ferrite-pearlite), 23 (martensite), and 28 (tempered martensite). As shown in Figure 1, it can be seen that the best sliding properties were obtained for the steel material of test piece No. 3.
[0094] Although one embodiment of the present invention has been described above, the above-described embodiment is merely an example for carrying out the present invention. Therefore, the present invention is not limited to the above-described embodiment, and the above-described embodiment can be appropriately modified and carried out without departing from the spirit of the present invention.
Claims
1. A steel material for sliding parts, comprising: The chemical composition, in mass%, is C: 0.42-0.48%, Si: 0.05-0.60%, Mn: 0.60-0.90%, P: 0.03% or less, S: 0.035% or less, Al: 0.005-0.060%, N: 0.001 to 0.020%, Cr: 0.10-0.35%, The balance is Fe and impurities. In at least a part of the steel material for sliding parts, a structure from the surface to a depth of at least 10 μm contains pearlite at a volume fraction of 30 to 80%, at least one of martensite and bainite, and ferrite, In the portion, the lamellar spacing of the pearlite from at least the surface to a depth of 10 μm is 90 to 200 nm; The portion has a Vickers hardness of Hv270 to 300 at least from the surface to a depth of 10 μm.
2. The sliding part steel material according to claim 1, A steel material for sliding parts, wherein a volume fraction of the pearlite is 61 to 80%, a sum of a volume fraction of the martensite and a volume fraction of the bainite is 3 to 30%, and a volume fraction of the ferrite is 3 to 32%.
3. A steel material for sliding parts, comprising: The chemical composition, in mass%, is C: 0.35-0.41%, Si: 0.05-0.60%, Mn: 1.35-1.65%, P: 0.03% or less, S: 0.070% or less, Al: 0.005-0.060%, N: 0.001 to 0.020%, Cr: 0.10-0.35%, The balance is Fe and impurities. In at least a part of the steel material for sliding parts, a structure from the surface to a depth of at least 10 μm contains pearlite at a volume fraction of 30 to 80%, at least one of martensite and bainite, and ferrite, In the portion, the lamellar spacing of the pearlite from at least the surface to a depth of 10 μm is 90 to 200 nm; The portion has a Vickers hardness of Hv270 to 300 at least from the surface to a depth of 10 μm.
4. The steel material for sliding parts according to claim 3, The steel material for sliding parts, wherein the lamellar spacing of the pearlite is 150 to 200 nm.
5. A steel material for sliding parts according to any one of claims 1 to 4, A steel material for sliding parts, in which the friction coefficient in said portion is 0.25 or less.
6. A method for producing a steel material for sliding parts according to claim 1 or 2, Heating the material to a temperature of 720 to 770°C; and cooling the material so that the average cooling rate in the temperature range from the heating temperature to 250°C is 40.0 to 50.0°C / sec.
7. A method for producing a steel material for sliding parts according to claim 3 or 4, A step of heating the material to a heating temperature of 720 to 950°C; and cooling the material so that the average cooling rate in the temperature range from the heating temperature to 250°C is 2.0 to 7.0°C / sec.
Citation Information
Patent Citations
Manufacture of fiberrformed sheetlike substance with high molecular elastic material stuck thereto
JP1981060220A
Sliding parts and their production
JP1989230746A
Hot forgings
JP2016098409A
Steel pipe for machine construction member excellent in machinability and manufacturing method therefor
JP2017048441A
Hot forging component and manufacturing method of hot forging component
JP2017066475A